PENGARUH POSISI BUAH PADA TANAMAN DAN PENGERINGAN BENIH TERHADAP PERKECAMBAHAN DAN PERTUMBUHAN BIBIT TANAMAN KAKAO (Theobroma cacao L.) - purnadi purnadi (AGRONISMA, 2021)
Cocoa is one of the plantation commodities of the Indonesian economy. In the cultivation of cocoa plants there are several things that must be considered, especially the use of the right seeds. (Darmoseputro, 1976). This study was conducted to determine how the growth of cacao seedlings affects the effect of different fruit positions on the plant and seed drying. This study used a two-factor Randomized Block Design (RAK) with treatment as a group consisting of 6 treatments, namely cropping patterns (B1P1, B1P2, B2P1, B2P2, B3P1, B3P2). The results showed that growth in the B1P1 treatment showed the highest value on the plant height parameter, while in the B1P1 and B2P2 treatments the highest value on the fresh weight of the root and the dry weight of the roots, while the parameters of germination percentage, number of leaves, leaf area, root dry weight and root dry weight. There was no significant effect on root dryness due to high rainfall which hampered the formation and growth of cacao seedlings.